RADIATION DIAGNOSIS OF RARE FORMS OF RESPIRATORY ORGAN SARCOIDOSIS - A. A. Speranskaya; O. P. Baranova; M. A. Vasilyeva; I. V. Amosov (Вестник рентгенологии и радиологии, 2018)
Objective: to evaluate the clinical and radiological features of rare forms of sarcoidosis of the respiratory organs (SRO).Material and methods. In 2006 to 2016, the Research Institute of Interstitial and Orphan Lung Diseases followed up 599 patients with sarcoidosis. 36 patients (6.0%) of them had atypical clinical and radiation manifestations that did not correspond to the traditional radiation pattern and the existing X-ray classification of SRO. Stages 2, 3, and 4 pulmonary sarcoidosis was diagnosed in 26, 7, and 3 patients, respectively. The patients’ mean age was 38.2±7.4 years (the female/male ratio was 26:10). All the patients underwent traditional X-ray studies (radiography in two projections), high-resolution computed tomography (CT), complex external respiratory function examination, and echocardiography.Results. Analysis of the results of radiation examinations revealed the following rare forms of SRO: interstitial edematous, fibrous, and cavitary ones that had recognizable CT patterns. Each of these forms had clinical and functional features. In single cases, the CT pattern combined the features incompatible with the generally accepted classification (Stages 1 and 4 SRO); this was an offstage form. The features of the radiation pattern and clinical course required the differential diagnosis of these patients with more severe diseases (idiopathic pulmonary fibrosis, lymphogenic carcinomatosis, pulmonary edema, diffuse connective tissue diseases, pneumoconiosis, mycobacteriosis, and exogenous allergic alveolitis) and morphological verification.Conclusion. The accumulation of experience with clinical and radiological examination of patients with SRO revealed its rare forms that are difficult to diagnose and necessitate the development of new approaches to therapy policy.